Crime and Punishment: Deportation in the Levant in the Age of Assyrian Hegemony - Valk, Jonathan (Bulletin of ASOR, 2020)
Assyrian imperialism is closely associated with the practice of mass deportation. This practice has been explained by recourse to many different motivations. But can we hope to pinpoint the logic informing deportation rather than merely identifying its advantages? This paper surveys the evidence of deportation in the Levant in the period 745-620 b.c.e. Focusing on deportation in this circumscribed time and place enables a more concentrated account of its use. Deportation is generally argued to have served three broad ends: bolstering the supply of human resources in the Assyrian heartland, meeting particular strategic needs, and dealing with dissent. This paper finds that despite the many uses of deportation, it was first and foremost a punitive instrument intended to curb resistance to Assyrian hegemony. This punitive dimension constituted the foundation of Assyrian deportation in the Levant in the age of Assyrian hegemony.